Evaluation of antibiofilm activity of Thymus syriacus essential oil against clinically isolated MDR bacteria - Basem Battah; Anas Rajab; Lama Shbibe; Jagjit Singh Dhaliwal; Khang Wen Goh; Long Chiau Ming; Yaman Kassab; Abdelhakim Bouyahya; Mahibub Mahahamadsa Kanakal; Chadi Soukkarieh (Progress in Microbes and Molecular Biology)
Finding alternative strategies to confront bacterial resistance is an urgent need. Biofilm-forming bacteria have become a serious problem in medicine and industry. Bacteria can use biofilm as a mechanism of resistance against antibacterial drugs and avoid the immune system. The aim of this study was to evaluate the antibacterial activity of Thymus syriacus (T. syriacus) essential oil in a solid and liquid medium and to study its antibiofilm formation activity. The T. syriacus essential oil was extracted from the aerial parts of the plants. The minimum inhibitory concentrations (MIC) measurements were used to identify the antibacterial activity of the essential oil against multidrug-resistant strains Pseudomonas aeruginosa (P. aeruginosa), Klebsiella pneumonia (K. pneumonia), Streptococcus pneumonia (S. pneumonia) isolated clinically from blood infections. The microtiter plate was used in order to quantify biofilm formation by bacteria. The minimum inhibitory concentration (MIC) against the three clinically isolated strains (P. aeruginosa, K. pneumonia, S. pneumonia) were (3.12, 1.56, 3.12 µL/mL) respectively. The formation of biofilm by (P. aeruginosa, K. pneumonia, S. pneumonia) was reduced up to (43%, 50%, 60%) respectively, when the essential oil was applied at MIC concentrations for each strain. The observed antibacterial activity of T. syriacus essential oil was significant against antibacterial-resistant strains and antibiofilm formation activity was identified. The novelty of this study is we confirmed that the essential oil of T. syriacus exhibited not just antibacterial properties but also antibiofilm formation effect. More studies are needed in order to continue studying this oil and evaluate its other medicinal properties and toxicity.